2011
DOI: 10.1097/pdm.0b013e3181fc02b7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Patients With Stage III/IV (M0) Advanced Gastric Cancer, According to HER2 Status Assessed by Immunohistochemistry and Fluorescence In Situ Hybridization

Abstract: Despite recent advances in chemotherapy, the prognosis for patients with advanced gastric cancer (GC) or gastroesophageal junction cancer remains poor. Human epidermal growth factor receptor 2 (HER2) is a novel target for biologic therapy in metastatic GC. We analyzed the association between HER2 overexpression and the clinicopathologic characteristics of advanced GC. Formalin-fixed, paraffin-embedded tumor samples were collected from patients with stage III or to IV (M(0)) GC who subsequently underwent curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 1 publication
6
19
1
1
Order By: Relevance
“…Similarly, in the ToGA trial, tumor with HER2 overexpression was reported to be more common in patients with a well-differentiated tumor histology [17][18][19]21]. Actually, well-differentiated tumor histology was significantly related to greater age, male gender, and an expansive growth pattern of the tumor in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similarly, in the ToGA trial, tumor with HER2 overexpression was reported to be more common in patients with a well-differentiated tumor histology [17][18][19]21]. Actually, well-differentiated tumor histology was significantly related to greater age, male gender, and an expansive growth pattern of the tumor in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 71%
“…Despite the increasing importance of this relationship, the relationship between HER2 overexpression and tumor biology in cases of gastric cancer still remains to be elucidated. Based on the results of the ToGA trial, several studies have evaluated HER2 overexpression in esophagogastric cancer using validated criteria [17][18][19][20][21][22]. The frequency of HER2 overexpression has been reported to be 9-16 %, consistent with the results of two major reviews of previous studies [4,9].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the study carried out by Orita et al (1997) HER2 positivity was associated with poorer survival results in gastric cancer patients. Another study further confirmed the shorter survival of HER2-positive patients, which had a 5-year survival of 29% compared to 47% HER2-negative patients (Im et al, 2011). Other studies reported similar findings (Czyzewska et al, 2009, Nakajima et al, 1999.…”
Section: Discussionmentioning
confidence: 55%
“…Trastuzumab is a monoclonal antibody targeted against the HER2 protein (Im et al, 2011). The ToGA study confirmed the survival benefits of trastuzumab in combination with chemotherapy compared with chemotherapy alone as a first line of treatment for patients overexpressing HER2 in advanced gastric or GEJ cancer (Bang et al, 2010).…”
Section: Discussionmentioning
confidence: 89%